Relationship between body weight and linear body measurements in boer goats. - Kamarudin, Nor Azhani; Omar, Mohamed Ariff; Marimuthu, Murugaiyah (2011)
Fifty-five Boer goats from a private farm located at Kg Pulau Meranti, Mukim Dengkil, Puchong, Selangor was sampled to examine the relationship between body weight and linear body measurements (body length, height at withers and heart girth). The goats were of four age groups: Group 1 (4-12 mo), Group 2 (13-18 mo), Group 3 (19-24 mo) and Group 4 (25-36 mo). Body weight and linear body measurements (body length, height at withers and heart girth) were taken during a 7-d period in December 2010. The body weight and linear body measurements were not significantly (p>0.05) different between male and female goats but were significantly(p<0.05) different among age groups. Male goats were heavier in weight, longer in body length, taller in height at withers and larger in heart girth compared to the female goats. Pearson’s coefficient of correlation showed positive, high and significant correlation between body weight and linear body measurements and also among the body measurements.A simple linear regression equation with a high coefficient of determination (R² = 0.948) using heart girth to predict body weight of Boer goats was also derived